Analisis Semiotika, Arti ‘Ingat Pesan Ibu’ Dalam Kampanye Penegakan Protokol Kesehatan Untuk Mengatasi Penularan Covid -19 - Kurniawan, Herik (Jurnal Media Komunikasi, 2025)
In October, after seven months since President Joko Widodo's first case announced the first Indonesian citizen to be exposed to Covid-19, Satuan Tugas Penanganan Covid-19 conducted a health protocol campaign in collaboration with the band Padi Reborn. Padi Reborn performed a song entitled “Ingat Pesan Ibu” by one of its personnel, Piyu. Mother and music are universal, making it easier to convey campaign messages to break the chain of spreading the virus. This study used a qualitative method with Ferdinand De Saussure's semiotic analysis. The marker in this song is to remember the mother's message, and the sign is to discipline the health protocol by obediently using a mask, washing hands, and maintaining distance when interacting.